2019
DOI: 10.1111/1469-8676.12675
|View full text |Cite
|
Sign up to set email alerts
|

Re‐searching access: what do attempts at studying migration control tell us about the state?

Abstract: Contributors to this special issue realised that reflecting on experiences of getting access (or not) can tell us something important about the institutions we aimed to study and, more broadly, about the migration control field. Put differently, attempts at approaching and approximating state actors within a charged field exposed us to some of its most fundamental organising principles. We have, therefore, set ourselves the task in this issue of SA/AS to ask and answer the following question: What do attempts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 44 publications
0
24
0
1
Order By: Relevance
“…The SBG is part of the ‘migration control field’, which is difficult for researchers to access (Kalir et al 2019 ). Despite concerns about increasing workload, we were quickly granted an interview with the head of the SBG.…”
Section: Methodsmentioning
confidence: 99%
“…The SBG is part of the ‘migration control field’, which is difficult for researchers to access (Kalir et al 2019 ). Despite concerns about increasing workload, we were quickly granted an interview with the head of the SBG.…”
Section: Methodsmentioning
confidence: 99%
“…This would later lead to the provision of the legal transcripts of the sentencing hearing. As previous studies on immigration have shown (Kalir et al, 2019) understanding the routes through which we can access people and institutions that exercise control over others tells us something about how these institutions work. Making explicit my own racial positioning in that courtroom that felt so unavoidably white, informs what conversations I had access to and how I analysed the empirical material presented in this article.…”
Section: Writing On Race As a White Scholarmentioning
confidence: 99%
“…The anthropology of the state is central to a special issue of Social Anthropology which examined issues around access experienced by anthropologists in relation to the state functions, systems and actors deployed in response to the migration ‘crisis’ as it is defined by the global North. Driven by the sense that within the field of migration and its control might be manifested some of the state’s most fundamental organising principles, the research projects highlighted in the preface (Kalir et al 2019) attempt to bring a comparative perspective to a highly contested and scrutinised issue. The management of undesired others, within a field which includes state agencies, parastate and international organisations, local, national and international NGOs as well individual actors – all of whom might be potentially hostile to researchers likely to produce critical accounts that might reflect negatively on their activities – provides the context for a cumulative synthesis.…”
Section: Borders Bureaucracy and Everyday Ethicsmentioning
confidence: 99%